2017
DOI: 10.1002/ecs2.1629
|View full text |Cite
|
Sign up to set email alerts
|

Plastic response by a small cervid to supplemental feeding in winter across a wide environmental gradient

Abstract: Supplemental feeding for ungulates is a widespread practice in many human‐dominated landscapes across Europe and North America, mainly intended to seasonally support populations. Surprisingly, little consideration was given so far to the effect of supplemental feeding on ungulate spatial ecology at a large scale, in management and conservation studies. Analyses of the main ecological drivers influencing the use of supplemental feeding sites by ungulates across a gradient of abiotic and biotic factors are curre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
35
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 72 publications
(183 reference statements)
2
35
0
Order By: Relevance
“…Indirect and direct anthropogenic factors can alter the cost-benefit balance of seasonal migration for partially migratory ungulate populations (Middleton et al 2013). For example, supplementary feeding in winter is widely practiced across Europe (Ossi et al 2017) and has been shown to alter behavior of elk in terms of distance migrated, the timing of arrival to, duration on, and departure from summer ranges (Jones et al 2014). Furthermore, besides the benefits of access to higher quality forage, migration may also result in demographic benefits due to the avoidance of mortality risk (Fryxell et al 1988, Eggeman et al 2016.…”
Section: Discussionmentioning
confidence: 99%
“…Indirect and direct anthropogenic factors can alter the cost-benefit balance of seasonal migration for partially migratory ungulate populations (Middleton et al 2013). For example, supplementary feeding in winter is widely practiced across Europe (Ossi et al 2017) and has been shown to alter behavior of elk in terms of distance migrated, the timing of arrival to, duration on, and departure from summer ranges (Jones et al 2014). Furthermore, besides the benefits of access to higher quality forage, migration may also result in demographic benefits due to the avoidance of mortality risk (Fryxell et al 1988, Eggeman et al 2016.…”
Section: Discussionmentioning
confidence: 99%
“…Observational studies have suggested that, as browsers with limited fat reserves 87 (Andersen, Gaillard, Linnell, & Duncan, 2000), roe deer exhibit a tight association between 88 movement and resource dynamics (Ossi et al 2017) with a strong plasticity to adapt its resource 89 acquisition at different spatio-temporal scales (De Groeve et al, 2019; Morellet et al, 2013;90 Peters et al, 2017). In contrast to group-living ungulates, the foraging decisions of roe deer are 91 expected to be clearly expressed at the level of individuals.…”
mentioning
confidence: 99%
“…The experiment was conducted between January and April, when roe deer use of 145 supplemental feeding is the most intense (Ossi et al, 2017), for three consecutive winters (2017,146 2018 and 2019). We implemented the experiment on 18 individuals, including five recaptures 147 and two deployments spanning two winters, leading to a total of 25 animal-years (21 adults: 15 148 females, 6 males; 4 yearlings: 2 females, 2 males; sample size n=4, 11 and 10 in 2017, 2018 and 149 2019 respectively; see Appendix S2 for details).…”
mentioning
confidence: 99%
“…Recent research has begun to analyse behavioural responses of wild ungulates to hunting pressure(Benhaiem et al, 2008;Lone, Loe, Meisingset, Stamnes, & Mysterud, 2015;Thurfjell, Spong, & Ericsson, 2013) and management practices(Ossi et al, 2017). Human presence and topography had also no apparent effect on roe deer expansion.…”
mentioning
confidence: 99%